A Model Shows Utility in Predicting Postoperative Recurrence and Distant Metastasis in Curatively Resected Esophageal Squamous Cell Cancer. (29th May 2019) - Wang, Weidong; Chen, Yongqiang; Zhang, Xuewen; Xi, Kexing; Feng, Xiaoli; Zhang, Lanjun
After curative treatment of esophageal squamous cell cancer (ESCC), patients are at high risk for recurrence. The objective of this study was to develop an index with a high sensitivity and specificity to predict ESCC patients' recurrence and prognosis. A retrospective analysis was conducted on consecutive patients with EC who underwent esophagectomy. In total, 1417 patients were included in the current investigation. In total, 770 patients were included in the current study's exploratory group. Alcohol consumption, TNM classification, number of lymph node station metastases, and number of lymph node metastases were significantly correlated with recurrence. Multivariate logistical regression analysis resulted in the development of an equation for predicting recurrence and prognosis (REEC). When using the REEC value to predict recurrence, the cutoff value was 1.095, the area under the curve (AUC) values of the REEC were 0.68 ( p < 0.001) in the Exploratory Group and 0.65 ( p < 0.001) in the Validation Group, and the sensitivity and specificity were 76.68% and 51.18%, respectively. When using the REEC value to predict prognosis, the cutoff value was 1.215, the AUC values of the REEC were 0.65 ( p < 0.001) in the Exploratory Group and 0.64 ( p < 0.001) in the Validation Group, and the sensitivity and specificity were 73.12% and 50.67%, respectively. In the Exploratory Group, when the REEC value was >1.095, patients had a longer median overall survival (OS) and median disease-free survival (DFS) than those whose REEC value was < 1.095 (70.01±2.01 months versus 50.92±2.85 months and 75.66±1.35 months versus 53.68±2.81 months, respectively, p < 0.001). The differences were confirmed to still exist in the Validation Group (48.12±1.47 vs 32.68±2.53 months and 55.61±1.32 vs 35.68±2.73 months respectively, p < 0.001).This study reported an index that can predict esophageal cancer recurrence and prognosis, and its use can benefit patients.